Study guides

☆☆

Q: 4x2 - 0x - 25

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x2 - 10x + 25 = 0(x - 5)(x - 5) = 0x - 5 = 0x = 5

(2x - 5)(2x - 5)

x2 - 5x = 0x (x - 5) = 0x = 0andx = 5

4x2 + x2 = 8 + x2

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

Related questions

(2x + 5)(2x - 5)

(2x - 3)(2x + 3)(2x-3)(2x+3)

This is an incomplete quadratic equation. Drop the 0X, as it is superfluous. 4X^2 -25 = 0 X^2 =25/4 X = +/- sqrt(25/4) X = +/- (5/4) check 4(5/4)^2 -25 = 0 true 4(-5/4)^2 - 25 = 0 also true

4x2+20x+25 (2x+5)^2

x2 - 10x + 25 = 0(x - 5)(x - 5) = 0x - 5 = 0x = 5

We're on it . . .6x3 + 4x2 = 2xSubtract 2x from each side:6x3 + 4x2 - 2x = 0Divide each side by 2:(Don't divide by 'x' ... you'll lose a root.)3x3 + 2x2 -x = 0Factor the left side:x (3x2 + 2x - 1) = 0x (3x - 1) (x + 1) = 0x = 0x = 1/3x = -1

c = 25 4x2 + 20x + 25 (2x + 5)(2x + 5)

(2x + 5)(2x - 5)

The discriminant is 0.

0x-34 = -34

(2x+5)(2x+5)

(2x - 5)(2x - 5)

People also asked